Synthesis and characterization of gel-type polymers via non-aqueous dispersion polymerization - Nur Najwa, Nazaruddin (2014)
In this work, synthesis and characterization of gel-type polymers via non-aqueous dispersion (NAD) was studied. The beaded polymers were produced via NAD have broad range of potential applications in many distinct area such as solid-phase extraction (SPE), chromatography, catalysis, etc. In this study, the experiment was divided into two sections namely one-stage NAD polymerzation and two-stage NAD polymerization. For one-stage NAD polymerization, all the monomers, initiator, stabilizer and co-stabilizer namely styrene, benzoyl peroxide, Triton X-305, and poly (N-vinylpyrolidone) (PVP), respectively were dissolved in ethanol in a 500 mL fournecked round bottom flask equipped with an overhead stirrer, condenser and a gas inlet. Then the reaction flask was placed on a heating mantle at 70°C and stirred mechanically at 125 rpm and the reaction was allowed for 24 hours. The particle obtained was washed with ethanol and methanol, then it was filtered using vacuum filtration on a 0.22 um nylon membrane filter and dry overnight in vacuum at 40°C. The results obtained were analyzed using optical microscope, CHNS analysis and Fourier-transform infra-red spectroscopy (FTIR). The sample contained 78.386% of Nitrogen, 87.300% of Carbon, 8.113% of Hydrogen and 0.24% of Sulphur. Nitrogen content was high due to the impurities and contamination from the surrounding environment and also due to PVP may have not completely dissolved during the' polymerization which contributed to nitrogen content in particles. FTIR results shown that the polymer belongs to alkene group thus, C=C and C=O bonds portrayed that the crosslinking agent, EDGMA was successfully incorporated in-polymers. The polymer also contained C=H2 bond, belongs to the alcohol group. Based on these results, the geltype poly(styrene-co-EDGMA) polymer was successfully synthesised via non-aqueous dispersion (NAD) polymerization.